The neuroinfec-ous diseases profile in a specialist neurology centre in South Africa - Oosthuizen, Katryn Nell Cobie (Department of Medicine, 2025)
Objective: This study aimed to assess the burden of neuroinfectious diseases and describe the causes and presentation of neurological infections to a tertiary level hospital neurology service in South Africa. Methods: A retrospective electronic search of medical discharge records was conducted for adult patients admitted to the neurology ward over a two-year period, and patients with neuroinfectious diseases were identified. Diagnostic criteria were applied to classify patients according to the certainty of their neuroinfectious disease diagnosis. Results: Neuroinfectious diseases accounted for 15% of the 802 admissions to the neurology ward. The most common infectious aetiologies were tuberculosis (27%), syphilis (21%), neurological diseases related to HIV itself (19%), and HIV-associated opportunistic infections (10%). Diagnostic challenges were observed, with only 17% of cases having a definite diagnosis. The majority of patients with neuroinfectious diseases were young, with a median age of 38 years (IQR: 32-46), and 56% were HIV-positive. Morbidity was high, with prolonged hospitalisation (>2 weeks) and limited full recovery at discharge in 56% and 98% of patients, respectively. Conclusions: This study provides important insights into the burden and characteristics of neuroinfectious diseases encountered at an inpatient South African neurology service. The findings highlight the need for earlier testing for, and treatment of, infections such as HIV, tuberculosis, and syphilis. Increased investment in neurological services should be a health care priority, to enhance the management of neuroinfectious diseases and ultimately improve patient outcomes.